RELEVANSI AJARAN KEMANUSIAAN PADA AGAMA HINDU DENGAN AJARAN ISLAM - Aribah Al Nashir, Fikriana; Amanah, Nurul; Maliana Juwita, Almi; Triyantoro; Sobirin (Cahaya Ilmu Bangsa Institute, 2024)
The Indonesian nation, with its diversity of ethnicities, races, religions, and cultures, offers a unique perspective in the context of religion. Although the majority of its population practices Islam, the country also officially recognizes other religions, such as Christianity, Catholicism, Hinduism, Buddhism, Protestantism, and Confucianism. Based on the principles of Pancasila, the nation places a high value on humanity. However, in practice, this value is often overlooked in favor of individual, group, or organizational interests. Religion should serve as a guide to create order and harmony in life, but in reality, religious diversity can act as a unifying force or as a potential source of division. Humanitarian teachings in Hinduism are emphasized through the concept of Tri Hita Karana, which stresses the importance of maintaining harmonious relationships between humans and God, between humans and others, and between humans and the environment. Meanwhile, in Islamic teachings, humanity is illustrated through the concept of hablum minannas, which highlights the significance of interpersonal relationships. The principle of “humanizing humans” is a central focus, reminding every Muslim that they are brothers to fellow Muslims and have a moral responsibility not to harm or mistreat others. Although both religions teach high humanitarian values, in practice, these values are often neglected due to personal and group interests. Therefore, it is essential for Indonesian society to reflect upon and apply the humanitarian values taught by these religions in their daily lives. Keywords: Humanity; Hinduism; Islam